Pre-Service Teacher Professional Identity Formation: Narrative study on Indonesian Accounting Teacher Candidate - Syah, Muhammad Fahmi Johan; Janudin, Sharul Effendy; Mansor, Mahaliza; Fuadi, Djalal; Suranto, Suranto; Romadhoni, Defri Nur; Hafidah, Angelia Suci Nur (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
This research investigates the components of professional identity among prospective accounting teachers, a topic largely unexplored in existing literature. Conducted in Indonesia, the qualitative study adopts a narrative design with six participants from both private and public universities. Data collection involves participants independently recording narratives throughout their first to third years of study, capturing the evolution of their professional identity. Results reveal a progression in professional identity formation over the three years. In the initial year, emphasis is on instructional abilities. By the second year, a notable shift occurs, with elements such as multitasking, game-based teaching, and character values gaining prominence. Furthermore, flexibility, agility, sensitivity, and tech savvy emerge as identity components. The third year marks a significant transformation, with a focus on soft skills, time management, and a sense of responsibility as central components of professional identity for prospective accounting teachers. It is crucial to acknowledge that these components remain subject to further evolution with continued analysis. The study recommends subsequent research utilizing quantitative methods, specifically exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), to provide a more comprehensive understanding of the identified professional identity components. This research contributes to the broader discourse on professional identity, shedding light on the nuanced development within the context of prospective accounting teachers.